Deformation and fracture behaviour of electroplated Sn–Bi/Cu solder joints - Goh, Y.; Haseeb, A.S. Md. Abdul; Liew, H.L.; Sabri, M.F.M. (Kluwer (now part of Springer), 2015)
This work utilizes the lap shear test to investigate the shear strength and fracture behaviour of electroplated and reflowed Sn–Bi/Cu lead-free solder joints. Particular emphasis is given on the effects of reflow temperature on the interrelationships among the interfacial intermetallic compound (IMC) morphology, shear strength and the fracture mechanism of the solder joints. Single-lap shear specimens are prepared by joining two commercially pure Cu substrates with electroplated Sn–Bi solder of about 50 µm thickness. The geometry of the lap shear specimen is designed to minimize the differences between far-field and actual responses of the solder. Three reflow temperatures (200, 230 and 260 °C) are used to investigate the effects of reflow temperature on the microstructure and shear strength of the solder. The specimens are loaded to failure at a strain rate of 4 × 10−4/s. Elemental mapping of the fracture surface is performed with field emission scanning electron microscope coupled with energy dispersive X-ray spectroscopy. A reflow temperature of 200 °C yields prism-like interfacial IMC morphology, while higher reflow temperatures of 230 and 260 °C yield scallop-like interfacial IMC morphology. The shear strength and elastic energy release, U, of the solder joints increase with increasing reflow temperature. Fractographs of the failed joints suggest that the fracture mechanism is dependent on the interfacial IMC morphology, where solder joints with prism-like interfacial IMC fail within the bulk solder and solder joints with scallop-like interfacial IMC failed with a mixture of bulk and interfacial fracture.